Determinants of Elderly Income in Indonesia During the Covid-19 Pandemic - Kornelius, Yobert; Parinding, Kalvin Albert; Ustadi, Muna Norkhairunnisak (Universitas Pendidikan Ganesha, 2024)
This study aimed to determine the factors that influence the income of the elderly during the Covid-19 pandemic. This study uses a quantitative approach with a panel data design. The data used are macro data issued by the Central Statistics Agency in 2019, 2020 and 2021 (Covid-19 pandemic period). The results of the study showed a significant decrease in the average income of the elderly both nationally and in each province during the COVID-19 pandemic in 2019 - 2021. There was a decrease in the average income of the elderly in 2019 - 2020 by 6.92 percent and 7.02 percent in 2020 - 2021. The results of multiple regression analysis using panel data showed that only one variable, the Allocation of elderly working time, had a significant effect on the average income of the elderly in Indonesia. The other three variables that did not have a significant effect were the number of elderly working, education and health of the elderly. During the COVID-19 pandemic, the main problem faced by the elderly is the implementation of social distancing and physical distancing, and the government's policy of Large-Scale Social Restrictions (PSBB) has a direct impact on reducing the Allocation of working time for the elderly, which then has an impact on reducing the income of the elderly.